Makna Dosa Menghujat Roh Kudus - Dominggus, Dicky (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2020)
This paper discusses the meaning of blaspheming the Holy Spirit. In the Bible, it is written that sin blasphemes the Holy Spirit as an unforgivable sin. This, of course, contrasts with the general understanding that Christ's death on the cross took away human sin. This article has a First goal, to find the meaning of sin to blaspheme the Holy Spirit. Second, find the reason why sin blaspheme the Holy Spirit cannot be forgiven. This research is a qualitative research with a grammatical historical approach. As for understanding the sin of blaspheming the Holy Spirit is an act of not recognizing Jesus as God.Tulisan ini membahas makna dari menghujat Roh Kudus. Di dalam Alkitab dituliskan Dosa menghujat Roh Kudus sebagai dosa yang tidak dapat diampuni.  Hal ini tentunya bertolak belakang dengan pemahaman umum di mana kematian Kristus di kayu salib sudah menghapus dosa manusia. Artikel ini memiliki tujuan Pertama, menemukan arti dari dosa menghujat Roh Kudus. Kedua, menemukan alasan mengapa dosa menghujat Roh Kudus tidak dapat diampuni. Penelitian ini merupakan penelitian kualitatif dengan pendekatan historikal gramatikal. Adapaun pemahaman dari dosa menghujat Roh Kudus merupakan tindakan tidak mengakui Yesus sebagai Allah.